Arnold Chiari Malformation With Sponastrime (Spondylar and Nasal Changes, With Striations of the Metaphyses) Dysplasia: A Case Report. Issue 18 (May 2016) - Jeong, Je Hoon; Lee, A Leum; Cho, Sung Yoon; Jin, Dong Kyu; Im, Soo-Bin
Abstract : Abstract: SPOndylar and NAsal changes, with STRIations of the Metaphyses (SPONASTRIME) dysplasia (SD) is a dwarfing autosomal recessive syndrome, characterized by a variety of clinical and radiographic features, which form the basis for diagnosis. We describe the presentation of an Arnold Chiari malformation in a patient with a clinical diagnosis of SD. The malformation was successfully treated by decompression of the foramen magnum and elevation of the cerebellum, with complete resolution of pain. We report a rare case of Arnold Chiari malformation in a patient presenting with clinical and radiographic features strongly suggestive of SD and be successfully treated.